Achieving sustainable development goals through common-good HRM: Context, approach and practice - Aust, Ina; Cooke, Fang Lee; Muller-Camen, Michael; Wood, Geoffrey (Sage, 2024)
This introduction to the special issue Achieving Sustainable Development Goals through Common-Good HRM: Context, approach and practice draws the links between the United Nations Sustainable Development Goals (SDGs), the concept of Common-Good HRM and the practice of human resource management (HRM) to extend intellectual and empirical insights into this important field. Particular attention is accorded to the collective social and environmental dimensions of SDGs and the place of HRM in contributing to the ‘common good’ within and beyond the workplace. Firms may create space and incentives for HRM to promote sustainability, or actively work to constrain meaningful action in this regard. This collection brings together a broad cross-section of articles dealing with the SDGs and HRM, identifying emerging common ground and contestation as a basis for future HRM theory building, empirical enquiry and practice.
Keywords: Common-Good HRM; Sustainable Development Goals; Sustainability Reporting; Sustainable Human Resource Management; HRM Theory